THE PROBLEM OF CITIZENSHIP IN THE RUSSIAN EMPIRE, STAGES OF DEVELOPMENT OF LEGISLATION TO FOREIGNERS (SECOND HALF OF XVII - BEGINNING OF XIX C.) - Vladimir V. Parkhomenko (Вестник Северо-Кавказского федерального университета, 2022)
This article studies the problems faced by foreigners when taking the citizenship of the Russian Empire. Changing the legal framework relating to the issue analyzed and divided into several periods.